Silyl Esters as Reactive Intermediates in Organic Synthesis - D’Amaral, Melissa C.; Andrews, Keith G.; Denton, Ross; Adler, Marc J. (Synthesis, 2023)
Silyl esters have been exploited as metastable reaction intermediates, both purposefully and unintentionally, since at least the 1960s. Their reactivity is broadly related to the substituents on the silicon, and in this way their properties can be readily modulated. Silyl esters have unique reactivity profiles that have been used to generate downstream products of a range of functionalities, and because of this many excellent methods for the synthesis of a variety of value-added chemicals have been developed. Furthermore, because of the frequent use of hydrosilanes as terminal reductants in catalytic processes, silyl ester intermediates are likely more commonly utilized by synthetic chemists than currently realized. This review comprehensively summarizes the reactions known to take advantage of reactive silyl ester intermediates and discusses examples of catalytic reactions that proceed in an unanticipated manner through silyl ester intermediates.1 Introduction2 Synthesis of Silyl Esters3 Making Amides from Silyl Esters3.1 Amidation Using Chlorosilanes3.2 Amidation Using Azasilanes3.3 Amidation Using Oxysilanes3.4 Amidation Using Hydrosilanes3.5 Amine Formation via Amidation/Reduction3.6 Miscellaneous4 Mechanistic Investigations of Amidation4.1 Mechanism of Amidation Using Chlorosilanes4.2 Mechanism of Amidation Using Hydrosilanes4.3 Mechanism of Amidation Using Oxy- or Azasilanes5 Making Esters from Silyl Esters6 Making Aldehydes, Alcohols, Amines, and Alkanes via Reduction6.1 Aldehyde Synthesis by Metal-Free Reduction6.2 Aldehyde Synthesis by Metal-Mediated Reduction6.3 Alcohol Synthesis by Metal-Mediated Reduction6.4 Amine Synthesis6.5 Alkane Synthesis by Metal-Free Reduction7 Making Acid Chlorides from Silyl Esters8 In Situ Generated Silyl Esters and Ramifications for Catalysis9 Conclusion
Keywords: silyl ester; carboxylic acid; organosilanes; amidation; reduction